Manajemen Ballast Water untuk Mencegah Pencemaran Lingkungan Laut di Kapal MT.Timur Laut Mas 2 - Ramayanti Ramayanti (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2025)
The implementation of ballast water management is a very important strategic step in preventing marine environmental pollution, because ship ballast water often becomes a route for the spread of invasive alien species that have the potential to disrupt the balance of the ecosistem, harm the maritime economic sector, and endanger human health. This study focuses on ballast water management practices on the MT Timur Laut Mas 2 ship, with the aim of assessing how the procedures are implemented in order to prevent the entry of alien species, reviewing the implementation of both international and national regulations, and evaluating the performance of the Ballast Water Management Sistem (BWMS) technology applied. This study uses a descriptive qualitative method based on a case study, with data collection through interviews with ship crews and company management, direct observation on board the ship, technical documentation, and a review of supporting literature. The results of the study show that the implementation of the IMO Ballast Water Management Convention (BWMC) regulations on ships has been realized through the preparation of a Ballast Water Management Plan, detailed recording in the Ballast Water Record Book, and the use of a BWMS that relies on filtration technology and ultraviolet radiation. However, the implementation still encounters obstacles in the form of limited crew understanding of system operation, variations in water quality along the shipping route that affect filtration effectiveness, and technical obstacles in equipment maintenance. Therefore, a combination of compliance with international regulations, improving crew competency through continuous training, and optimizing sistem operations are key factors in strengthening the effectiveness of ballast water management. These findings confirm that the application of modern technology in accordance with regulatory requirements can enhance marine ecosistem protection while ensuring the sustainability of the maritime industry, thus positively contributing to environmental sustainability and the stability.